Avaliação da capacidade imunomoduladora de extratos de própolis verde em animais vacinados com herpesvírus suíno tipo 1 (SuHV-1) ou herpesvírus bovino tipo 5 (BoHV -5) - Fischer, Geferson (2007)
Vaccine formulation often requires the use of adjuvants which enhance or potentiate humoral and/or cellular responses. Nowadays, many vaccines are formulated with substances such as aluminum hydroxide or oily emulsions, specific for veterinary use. However, the interest on the evaluation of natural substances with adjuvant potential like plant extracts has grown. Propolis produced by honey bees from exudates collected from plants has call the attention of researchers due to several bioactive properties reported, such as antiviral, antiinflamatory and antitumoral action. In addition, although the mechanism of action remains unknown, propolis presents activity on the immune system. The aim of this study was to evaluate the immunomodulator activity of an ethanolic extract of Brazilian green propolis, when used as adjuvant in inactivated vaccines against swine herpesvirus type 1 (SuHV-1) or bovine herpesvirus type 5 (BoHV-5). The addition of 5 mg/dose of the extract to a vaccine with aluminum hydroxide against SuHV-1 increased the humoral immune response of mice, when compared to the same vaccine without propolis (P<0,01). This effect was more evident when the vaccine was diluted (1:4 and 1:8). The raise in neutralizing antibodies titer, expressed in log2, went from 3 to 4.48 and 2.18 to 4.48, respectively, suggesting that the smaller the antigenic mass or less immunogenic the antigen, more pronounced is the adjuvant effect of propolis. When propolis was used on its own with the antigen, an increase in the titer of neutralizing antibodies determined by seroneutralization was not observed. Besides increasing the humoral immune response, the use of propolis also increased the cellular response, increasing mRNA synthesis of IFN-? in mice splenocytes, measured by RT-PCR. This increase was also observed in the group of animals immunized only with antigen and propolis, unlike the effect observed on the humoral response. The adjuvant effect of propolis was also demonstrated when mice were challenged with 31.6 lethal doses of SuHV-1, 21 days after the second inoculation. The addition of propolis to the vaccine with aluminum hydroxide increased the percentage of protected animals, especially in the higher dilutions, comparing to the vaccine without propolis. Similar result was observed in the group of animals vaccinated only with propolis and antigen. The association of 40 mg/dose of ethanolic extract of green propolis to the oily vaccine against BoHV-5 increased titer of bovine neutrali zing antibodies (P<0,01), when compared to a vaccine without propolis. Thirty days after the second dose the titer went from 35 to 54, and after the third dose it increased from 43 to 67. In addition, there was an increase in the percentage of animals with titer above 32. The inclusion of 20 mg/dose of the extract did not alter the humoral response. The chromatographic analysis of propolis by HPLC showed high levels of phenolic compounds as artepillin C and cynamic acid derived, which may be the main substances with action on the immunologic system. Therefore, green propolis ethanolic extract acted as an adjuvant substance, increasing humoral and cellular immune responses in mice and humoral response in bovines, improving the efficiency of experimental vaccines.